Proteomic analysis of protein purified derivative of Mycobacterium bovis - Roperto, Sante (J Transl Med, 2017)
BACKGROUND: Tuberculin skin test based on in vivo intradermal inoculation of purified protein derivative from Mycobacterium bovis (bPPD) is the diagnostic test for the control and surveillance of bovine tuberculosis (bTB). METHODS: Proteomic analysis was performed on different bPPD preparations from M. bovis, strain AN5. Proteins were precipitated from bPPD solutions by TCA precipitation. The proteome of bPPD preparations was investigated by bottom-up proteomics, which consisted in protein digestion and nano-LC–MS/MS analysis. Mass spectrometry analysis was performed on a Q-exactive hybrid quadrupole-Orbitrap mass spectrometer coupled online to an Easy nano-LC1000 system. RESULTS: Three hundred and fifty-six proteins were identified and quantified by at least 2 peptides (99% confidence per peptide). One hundred and ninety-eight proteins, which had not been previously described, were detected; furthermore, the proteomic profile shared 80 proteins with previous proteomes from bPPDs from the United Kingdom and Brazil and 139 protein components from bPPD from Korea. Locus name of M. bovis (Mb) with orthologs from M. tuberculosis H37Rv, comparative gene and protein length, molecular mass, functional categories, gene name and function of each protein were reported. Ninety-two T cell mycobacterial antigens responsible for delayed-type hypersensitivity were detected, fifty-two of which were not previously reported in any bPPD proteome. Data are available via ProteomeXchange with identifier PXD005920. CONCLUSIONS: This study represents the highest proteome coverage of bPPD preparations to date. Since proteins perform cellular functions essential to health and/or disease, obtaining knowledge of their presence and variance is of great importance in understanding disease states and for advancing translational studies. Therefore, to better understand Mycobacterium tuberculosis complex biology during infection, survival, and persistence, the reproducible evaluation of the proteins that catalyze and control these processes is critically important. More active and more specific tuberculins would be desirable. Indeed, many antigens contained within bPPD are currently responsible for the cross-reactivity resulting in false-positive results as they are shared between non-tuberculous and tuberculous mycobacteria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-017-1172-1) contains supplementary material, which is available to authorized users.